2007
DOI: 10.1105/tpc.106.048413
|View full text |Cite
|
Sign up to set email alerts
|

ACTIN BINDING PROTEIN29 fromLiliumPollen Plays an Important Role in Dynamic Actin Remodeling

Abstract: Villin/gelsolin/fragmin superfamily proteins have been shown to function in tip-growing plant cells. However, genes encoding gelsolin/fragmin do not exist in the Arabidopsis thaliana and rice (Oryza sativa) databases, and it is possible that these proteins are encoded by villin mRNA splicing variants. We cloned a 1006-bp full-length cDNA from Lilium longiflorum that encodes a 263-amino acid predicted protein sharing 100% identity with the N terminus of 135-ABP (Lilium villin) except for six C-terminal amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 63 publications
(88 reference statements)
8
125
0
Order By: Relevance
“…Pharmacological disruption of actin and genetic manipulation of the actin regulatory system have revealed that the actin cytoskeleton is a major mediator of pollen tube growth (Gibbon et al, 1999;Chen et al, 2002;Cheung and Wu, 2004;Xiang et al, 2007). Furthermore, imaging of actin filaments has shown that distinct actin structures form in pollen tubes across different species.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological disruption of actin and genetic manipulation of the actin regulatory system have revealed that the actin cytoskeleton is a major mediator of pollen tube growth (Gibbon et al, 1999;Chen et al, 2002;Cheung and Wu, 2004;Xiang et al, 2007). Furthermore, imaging of actin filaments has shown that distinct actin structures form in pollen tubes across different species.…”
Section: Introductionmentioning
confidence: 99%
“…High and Low Speed Co-sedimentation Assays-A high speed co-sedimentation assay was used to determine the F-actin binding activity of GST-CROLIN1 following a published method (32).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence Microscopy and Electron Microscopy Visualization of F-actin-To visualize F-actin using fluorescence microscopy, the samples were labeled with Alexa 488-phalloidin (Molecular Probes), as described in a previously published method (32). F-actin was observed using a Leica DFC420C fluorescence microscope equipped with a 5-megapixel CCD and Leica Application Suite software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations